METHOD OF INTELLECTUAL PROCESSING OF THE STATE VIDEO INFORMATION RESOURCES FOR INCREASE OF THEIR SEMANTIC INTEGRITY IN SYSTEMS OF MONITORING OF CRISIS SITUATIONS - Баранник, Володимир Вікторович; Рябуха, Юрій Миколайович (Ukrainian Information Security Research Journal, 2015)
It is shown that development of infocommunication technologiesprovided creation of remote systems of collectinga video information on the basis of onboard complexes of aero monitoring (AM). It is shown that the video information(VIR) in such systems is used in interests of profiledepartments and makes state information a resource. It isproved that for safety of a video information for systemsof aero monitoring categories of availability and integrityhave the powerful importance. Problem aspects of theoreticalapproaches concerning processing of video data for increaseof their availability and integrity are analysed. Needof creation of theoretical base and methods for creation ofthe effective syntactic description of the contextual contentsof the video footage with use of intellectualization ofprocess of identification of video of scenes on degree oftheir semantic contents is stated. The method of intellectualprocessing of VIR taking into account an assessmentof degree of informational content of the semantic maintenanceof a video picture and the subsequent differentiatedprocessing directed on saving of planimetric information iscreated. Recommendations concerning synthesis of a metricsof an assessment of semantic complexity of the VIRsegment about its planimetric information are developed.The method of identification of degree of informationalcontent of the semantic contents of the video footage isunder construction.